A comparison between SMR and SSPC classification systems for the assessment of rock slope stability in the context of Pelotas Batholith, Canguçu, Rio Grande do Sul, Brazil. (October 2021) - Arab, Paola Bruno; Vieira, Leo; de Siqueira, Allan Felipe Rocha
Abstract: Rock mass classifications are a simple yet useful tool to provide a practical assessment of rock slope stability. Among the available classifications for this purpose, Slope Mass Rating - SMR (Romana, 1985) is the most commonly used. It is based on the basic Rock Mass Rating - RMR (Bieniawski, 1989) and on adjustment factors related to the geometry and method of excavation of rock slopes. While SMR is a discrete method, the Slope Stability Probability Classification - SSPC (Hack et al., 2002), a less-known classification, is a probabilistic one. SMR gives better results when applied to structural-controlled rock masses, while SSPC provides solutions for both structural-controlled and nonstructural-controlled rock masses. The aim of this study was to assess the stability of cutting slope sections by SMR and SSPC along a BR-471 Highway segment, in Canguçu, state of Rio Grande do Sul, Brazil. The chosen area lies in the Pelotas Batholith, a 400 km-length unit, whose geometry and structures are regionally controlled by transcurrent shear zones. The location is characterized by a subtropical climate with high humidity and rainfall along the year. The analysis showed that the rock mass is structural-controlled, and many of the sections analyzed present stability problems. Comparing the methodologies applied, SMR indicates ten geotechnical zones as unstable or completely unstable, while SSPC indicates six unstable ones, which are all related to sliding failure, including both planar and wedge failures. Both methods applied showed good results. Yet, adjustments regarding the original criteria have real potential to improve further analyzes in the area. For SMR, the main suggestions include: adjustment of kinematic analysis weight in comparison to the weight of RMRb features, adjustment of weathering grade weight in relation to IRS, and inclusion of weight for large scale roughness. The suggestions for SSPC regarding structural-controlled stability are: adjustment of the susceptibility to weathering weight, focusing on the weathering of discontinuities, and the inclusion of the effect of water percolation. Highlights: SMR and SSPC provide fair results in the south portion of Pelotas Batholith. Large scale roughness proved to be essential for the cutting slope stability. Weathering parameters of discontinuities are more relevant than a general one. The effect of water is relevant because of local topography and climate conditions. Adjustments on both SMR and SSPC can lead to more accurate results.